Immediate Effect of Abdominal Binder on Peak Expiratory Flow Rate (PEFR) in Chronic Obstructive Pulmonary Disease (COPD) Patients - Sheral Thomas Kachpile (International Journal of Allied Medical Sciences and Clinical Research, 2020)
The purpose of the study is to determine the immediate effect of abdominal binder on peak expiratory flow Rate (PEFR) in chronic obstructive pulmonary disease (COPD) patients. 30 subjects were selected as COPD as a diagnosis. All 30 subjects were checked for their peak expiratory flow rate (PEFR) by wright peak flow meter in sitting position.3 readings were taken and average of them was recorded. All 30 patients were then applied an abdominal binder in sitting position and checked for peak expiratory flow rate (PEFR).3 readings were taken and Average of them was recorded. The mean PEFR value after the application of abdominal binder and prior to application of abdominal binder was analysed and mean PEFR value showed significant increase after the application of abdominal binder. Thus this study says immediate effect of abdominal binder on peak expiratory flow rate in COPD patients is increase in peak expiratory flow rate (PEFR).